Economic Policies for Sustainable Development - Commemorative book marking the 20th anniversary of CINPE: Libro conmemorativo del 20 aniversario del CINPE - Zuñiga-Chávez, Guillermo (2018)
On the occasion of the 20th anniversary of the International Center for Economic Policy for Sustainable Development (CINPE) at the National University of Costa Rica, an international seminar entitled "Economic Policies for Sustainable Development" was held in November 2015. As a result of this commemorative activity, the book Economic Policies for Sustainable Development was published, which is the subject of this editorial and was presented to the community on February 28, 2018. This editorial discusses the scope of this publication, but above all, it sheds light on elements that would contribute to the discussion on public policy and sustainable development.